2009
DOI: 10.1590/s1413-86702009000300008
|View full text |Cite
|
Sign up to set email alerts
|

First survey for detecting the presence of human herpesvirus 8 infection (HHV-8) in Maputo, Mozambique

Abstract: Human herpesvirus 8 (HHV-8), the etiological agent of Kaposi's sarcoma (KS), is endemic in parts of the subSaharan, and KS has increased concomitantly with the HIV/AIDS epidemic. In Mozambique (MZ), no data concerning HHV-8 infection was available, thus the main of this work was to investigate, for the first time, the presence of HHV-8 infection in Maputo, MZ. Latent and lytic HHV-8-specific antibodies were assessed in blood samples from 189 individuals from the Central Hospital of Maputo, MZ, using "in-house"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Few data are available on the seroprevalence of and risk factors associated with HHV-8 infection in Mozambique. Only two preliminary studies have been conducted, and these studies present different results [Ceffa et al, 2007;Caterino-de-Araujo et al, 2009]. The reported heterogeneity in HHV-8 seroprevalence could be an artifact resulting from interlaboratory variability in the assays or may be due to variability in the age or characteristics of the analyzed population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few data are available on the seroprevalence of and risk factors associated with HHV-8 infection in Mozambique. Only two preliminary studies have been conducted, and these studies present different results [Ceffa et al, 2007;Caterino-de-Araujo et al, 2009]. The reported heterogeneity in HHV-8 seroprevalence could be an artifact resulting from interlaboratory variability in the assays or may be due to variability in the age or characteristics of the analyzed population.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, all of these variables could account for the discordant results that have been reported. For instance, one study used an ELISA that is available commercially to detect HHV-8 antibodies [Ceffa et al, 2007]; the other used an ''in house'' immunofluorescence assay [Caterino-de-Araujo et al, 2009]. In addition, differences in the characteristics of the participants, including age and gender and socioeconomic, demographic and clinical variables were observed between the studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An immunofluorescence assay (IFA) that detects antibodies specific for latent antigens (IFA‐LANA) has long been considered a reference serological test to detect HHV‐8 infection [Martin et al, 2000], and an IFA to detect lytic antigens (IFA‐Lytic) has been used in epidemiological surveys [Rezza et al, 1998; Leão et al, 2002; Pérez et al, 2006; Mohanna et al, 2007]. The Immunology Department of the Instituto Adolfo Lutz, a Public Health Laboratory in São Paulo, Brazil, has used these assays to identify at‐risk populations [Caterino‐de‐Araujo and Cibella, 2003; Cunha et al, 2005; Avelleira et al, 2006; Caterino‐de‐Araujo et al, 2003, 2007a,b, 2009; Magri et al, 2008] and to compare the frequency and titer of antibodies against latent and lytic antigens of HHV‐8 in clinically interesting populations [Magri et al, 2009]. These studies have identified high‐risk groups and patterns of antibodies for HHV‐8 of predictive value.…”
Section: Introductionmentioning
confidence: 99%